THE CHALLENGES OF DISTANCE LEARNING DURING THE COVID-19 PANDEMIC: THE CONTEXT OF LITHUANIAN PRE-SCHOOL TEACHERS' OPINIONS - Bilbokaitė-Skiauterienė, Ieva; Bilbokaitė, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The COVID-19 pandemic has brought unprecedented challenges to the education system. Since Lithuania has declared the state-level emergency in February 2020, imposed by quarantine, the educational process was organized in a distance mode. Distance learning, namely, was a platform that pre-schools used to meet the learning needs of children. The aim of this article is to review pre-school teachers’ opinions about the challenges of distance learning during the Covid-19 pandemic. The article describes the situation in Lithuanian pre-schools using distance learning during the lockdown. The authors analyse the main problems that pedagogues have faced with - lack of competence in the use of IT, poor support from management, inadequate material base, lack of time and teachers’ self-confidence, the low involvement of families.